Incongruencies between Indonesian and Korean Passive Voice Sentences (Makassar State University, 2022)
Abstract. Korean passive sentences are considered difficult to understand by Indonesians. Due to Indonesian language interference, ungrammatical Korean sentences are often produced by Indonesian. This study is aimed at analyzing the factors causing incongruity between Indonesian and Korean passive sentences. This research is descriptive qualitative study and the data are Indonesian simple passive sentences and equivalent forms in Korean. Both languages were analyzed using the theory of voice, passive prototype, and language typology by applying the contrastive and comparative methods. The finding results indicate that the causal factors can be traced back to differences Indonesian and Korean passive voice systems generated by the attributes both languages maintain, covering argument marking system, construction controller, subject selection criteria, agency coding, how the event is described, and sensitivity to animacy. Indonesian, which marks its core argument using word order, is a subject prominent language that prioritizes the argument’s syntactic function. The sentence constructions are controlled by the argument’s syntactic functions coded in the verb. Meanwhile, Korean, which indicates all arguments with case markers, is a topic and subject prominent language that emphasizes the argument’s inherent attribute. Korean sentence constructions are controlled by the argument’s inherent attributes, namely ANIMACY and CONTROL. Consequently, Indonesian passive sentences that do not align with Korean principles of Animacy Hierarchy and Control Degree are incongruent when translated into Korean passive sentences. The results of this study infer that the passive voice issue is not limited to the morpho-syntactic, but involves various levels of language and views of the world. Keywords: Indonesian and Korean passive sentences, voice modulation, language typology, Animacy, Degree of Control